Quantitative profiling of N 6 -methyladenosine at single-base resolution in stem-differentiating xylem of Populus trichocarpa using Nanopore direct RNA sequencing - Gao, Yubang; Liu, Xuqing; Wu, Bizhi; Wang, Huihui; Xi, Feihu; Kohnen, Markus V; Reddy, Anireddy S N; Gu, Lianfeng (Genome biology, 2021)
There are no comprehensive methods to identify N -methyladenosine (m A) at single-base resolution for every single transcript, which is necessary for the estimation of m A abundance. We develop a new pipeline called Nanom6A for the identification and quantification of m A modification at single-base resolution using Nanopore direct RNA sequencing based on an XGBoost model. We validate our method using methylated RNA immunoprecipitation sequencing (MeRIP-Seq) and m A-sensitive RNA-endoribonuclease-facilitated sequencing (m6A-REF-seq), confirming high accuracy. Using this method, we provide a transcriptome-wide quantification of m A modification in stem-differentiating xylem and reveal that different alternative polyadenylation (APA) usage shows a different ratio of m A.